2022
DOI: 10.3389/fimmu.2022.1026163
|View full text |Cite
|
Sign up to set email alerts
|

Association of antithrombin with development of trauma-induced disseminated intravascular coagulation and outcomes

Abstract: IntroductionTrauma activates the innate immune system to modulate hemostasis and minimize the damage caused by physiological bodily responses, including the activation of coagulation. Sufficiently severe trauma overwhelms physiological responses and elicits the systemic inflammatory response syndrome, which leads to the onset of disseminated intravascular coagulation (DIC), characterized by dysregulated inflammatory coagulofibrinolytic responses. Impaired anticoagulant mechanisms, including antithrombin, const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…In summary, following burn injuries, genetic variation perspectives indicate a somewhat heightened activation of negative regulatory mechanisms. This aligns with ndings from previous studies focusing on early trauma 24 ; however, further examination is required within the context of burn patients. Given the dynamic nature of burn injuries, the insights we have presented may necessitate additional validation through rigorous animal or clinical trials.…”
Section: Discussionsupporting
confidence: 88%
“…In summary, following burn injuries, genetic variation perspectives indicate a somewhat heightened activation of negative regulatory mechanisms. This aligns with ndings from previous studies focusing on early trauma 24 ; however, further examination is required within the context of burn patients. Given the dynamic nature of burn injuries, the insights we have presented may necessitate additional validation through rigorous animal or clinical trials.…”
Section: Discussionsupporting
confidence: 88%
“…In summary, following burn injuries, genetic variation perspectives indicate a somewhat heightened activation of negative regulatory mechanisms. This aligns with findings from previous studies focusing on early trauma 24 ; however, further examination is required within the context of burn patients. Given the dynamic nature of burn injuries, the insights we have presented may necessitate additional validation through rigorous animal or clinical trials.…”
Section: Discussionsupporting
confidence: 88%
“…97 A recent clinical study has also indicated that the correction of antithrombin activity may contribute to improving the outcomes of trauma cases. 98 Importantly, this study suggested that it is necessary to consider the type of hemorrhage (simple type bleeding or oozing type bleeding), the type of coagulation changes (DIC or not), and when antithrombin should be administered (acute phase or subacute phase) to effectively identify target populations that benefit from anticoagulant therapies. 98 Definite DIC diagnosis and confirmation of the existence of systemic pathologic hyperfibrin(ogen)olysis appear to be the initial steps in the treatment of DIC with a fibrinolytic phenotype.…”
Section: Prognosis and Treatmentmentioning
confidence: 99%